Peningkatan Minat Berobat ke Puskesmas melalui Analisa Faktor yang Mempengaruhi Minat Kunjungan: Increasing Interest in Going to the Health Center through Analysis of Factors Affecting Interest in Visits - Wiwik Suryandartiwi; Bobi Handoko; Muhammad Firdaus (Journal of Health, 2024)
Public Health Centers are part of the health service that aims to organize health and is responsible for health development in the work area. Interest in visiting a health center is one of the most important things in improving health services in the community. One of the factors that influence interest in visiting a health center is accreditation. However, the actual accreditation of health centers is not well known among the general public. People are more familiar with criteria such as the quality of human resources, economy, location, facilities and service time. The method used is a quantitative method with a survey approach at Rejosari Health Center, Tenayan Raya District, Pekanbaru City. The community who participated in filling out the questionnaire was 100 people, the people who filled out the questionnaire were adult men and women with an average age of 18-40 years. Based on the data obtained, it shows that the quality of human resources has a negative influence on the interest in visiting. Then the economy, location, facilities and time have a positive influence on the interest in visiting the health center by the community. The results of this study also show that the selected factors have a model fit with the interest in visiting shown by the r value of 75.3%. The linear equation model obtained in the analysis of factors affecting interest in visiting is Y = 0.211 - 0.116 X1 + 0.149 X2 + 0.063 X3 + 0.385 X4 + 0.046 X5+e.